PENGARUH KUALITAS PELAYANAN, PEMERIKSAAN PAJAK, PENGETAHUAN PERPAJAKAN DAN SANKSI PERPAJAKAN PADA KEPATUHAN WAJIB PAJAK RESTORAN - Sucandra, Inten Pratiwi; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 16 No 2 (2016), 2016)
Taxpayer compliance restaurants in the Badung regency has an important role to increase local revenues, because taxes restaurants in the Badung regency has a great potential for optimized acceptance. The purpose of this study was to determine the effect of service quality, tax audits, tax knowledge and tax penalties on taxpayer compliance restaurant. Methods of data collection in this study using survey method through a questionnaire. The samples used were 90 taxpayers restaurant which is calculated using the formula slovin the sampling method used is proportionate stratified random sampling. The data analysis technique used is multiple linear regression analysis. The results showed that the quality of service, tax audits, tax knowledge and tax penalties and significant positive effect on tax compliance restaurants in Department of Revenue/Pasedahan Agung Badung Regency.
Keywords: tax compliance, quality of service, tax audits, tax knowledge, tax penalties